Implementation of a DC Microgrid - Shaver, Lee (My University, 2017)
The first permanent electric grid powered only the homes and buildings in its immediate vicinity–much like microgrids, which are presently the focus of intense research and development. An area holding great promise for application of microgrids is electrification and grid improvement in the developing world. The potential of microgrids in this space is examined, and development of a system intended for this context is detailed. The Microgrid Energy Manager (MEM) system is proposed as a low-cost, scalable, modular system for quickly establishing microgrids with off-the-shelf components. Design of the system for interfacing with dc loads and sources is described, and tests of the system’s ability to monitor batteries, prioritize loads, and share battery capacity between interconnected microgrids are conducted. Finally, microgrid work done in partnership with students and faculty at the National Institute of Engineering in Mysuru, India is detailed. Goals of this work include establishing a live microgrid testbed on the NIE campus, and preparation of remote villages for permanent microgrids.
Professor Giri Venkataramanan, Major Advisor